DEVELOPMENT OF SKILLS OF PROSPECTIVE TEACHER STUDENTS IN USING LEARNING MEDIA THROUGH FIELD STUDY - Wahidin, Unang; Sarbini, Muhammad; Anggraeni, Wulan (Edukasi Islami: Jurnal Pendidikan Islam, 2024)
It is necessary to develop the skills of prospective teacher students in using various forms of learning media. This research aims: (1) to analyze the perception of prospective teacher students towards field study to school, (2) to analyze the level of understanding of prospective teacher students towards learning media subject matter, (3) to analyze the usefulness of field study for prospective teacher students in studying learning media courses. The research method used is qualitative with a descriptive type of study research—data collection techniques through complete observation, documentation, and structured interviews. The results showed (1) Perceptions of prospective teacher students towards field study to school: (a) Strongly disagree that learning media courses are only studied as the theory in class, (b) With field study to school, the material of learning media courses becomes more interesting. (2) The level of understanding of prospective teacher students towards learning media subject matter: (a) Through field study, prospective teacher students gain direct experience related to the use of various forms of learning media, (b) With field study make learning media subject material relevant, (c) Field study helps prospective teacher students easily understand learning media subject material. (3) Field study is helpful for prospective teacher students learning media course material. This research implies that developing a learning media lecture system is necessary through a field study of prospective teacher students in schools.